Identification and Verification of Potential Biomarkers in Gastric Cancer By Integrated Bioinformatic Analysis - Sun, Chenyu; Chen, Yue; Kim, Na Hyun; Lowe, Scott; Ma, Shaodi; Zhou, Zhen; Bentley, Rachel; Chen, Yi-Sheng; Tuason, Margarita Whitaker; Gu, Wenchao; Bhan, Chandur; Tuason, John Pocholo Whitaker; et al. (Frontiers in Genetics, 2022)
Background: Gastric cancer (GC) is a common cancer with high mortality. This study aimed to identify its differentially expressed genes (DEGs) using bioinformatics methods. Methods: DEGs were screened from four GEO (Gene Expression Omnibus) gene expression profiles. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed. A protein-protein interaction (PPI) network was constructed. Expression and prognosis were assessed. Meta-analysis was conducted to further validate prognosis. Receiver operating characteristics curve (ROC) was analyzed to identify diagnostic markers, and a nomogram was developed. Exploration of drugs and immune cell infiltration analysis were conducted. Results: Nine up-regulated and three down-regulated hub genes were identified, with close relations to gastric functions, extracellular activities, and structures. Overexpressed COL8A1, COL10A1, CTHRC1, and FAP correlated with poor prognosis. Area under curve (AUC) of ADAMTS2, COL10A1, COL11A1, and CTHRC1 were >0.9. A nomogram model based on CTHRC1 was developed. Infiltration of macrophages, neutrophils, and dendritic cells positively correlated with COL8A1, COL10A1, CTHRC1, and FAP. Meta-analysis confirmed poor prognosis of overexpressed CTHRC1. Conclusions: ADAMTS2, COL10A1, COL11A1, and CTHRC1 have diagnostic values in GC. COL8A1, COL10A1, CTHRC1, and FAP correlated with worse prognosis, showing prognostic and therapeutic values. The immune cell infiltration needs further investigations.